Calendar Aging of NCA Lithium-Ion Batteries Investigated by Differential Voltage Analysis and Coulomb Tracking. Issue 1 (1st January 2017) - Keil, Peter; Jossen, Andreas
Abstract : Calendar aging of lithium-ion cells is investigated by storing commercial 18650 cells with NCA cathode and graphite anode at different states of charge and temperatures. The resulting capacity fades are analyzed by differential voltage analysis (DVA) and coulometry. DVA reveals that the capacity fade results mainly from a shift in the electrode balancing due to a reduced inventory of cyclable lithium. Moreover, DVA confirms that the capacity fade strongly correlates with the anode potential. The observed loss of cyclable lithium is further analyzed by coulomb tracking, which stands for creating a continuous ampere-hour balance from all individual measurements performed with an examined cell and tracking the slippage of charging and discharging endpoints. It reveals the extent of anodic and cathodic side reactions during the storage periods and their effect on the inventory of cyclable lithium. Anodic side reactions, which are related to electrolyte reduction and passivation layer growth, can be identified as the main driver of capacity fade. Coulomb tracking also discloses that increasing cathodic side reactions can reduce the irreversible capacity fade, particularly for storage at very high SoC, which is likely to be misinterpreted as decelerated aging reactions. Evaluating also the reversible capacity fade prevents such a misconception.